Medidas assecuratórias na lei de lavagem de capitais: finalidade e aplicação do instituto face ao estado democrático de direito - Martins, Guilherme Pereira Gonzalez Ruiz (2013)
This dissertation intends to help the understanding of the Law of Money Laundering under an innovative approach, treating the context of a democratic state founded on the dignity of the human person and the influence of the criminal policy of emergency in the legislative process, which ultimately help to create with eminently repressive laws, drawing upon the misrepresentation of criminal procedural instruments to achieve the purposes of criminal prosecution, perpetrating a maneuver within the limits of the law to punish the state. The Money Laundering Act, from the standpoint of international treaties and conventions that Brazil is committed to meeting reaches the constriction and its confiscation of property as a means of containment of organized crime, however, imposed the most authoritarian procedural schemes among existing in the Brazilian law, allowing the constriction of goods through to transform the preservative measures in an early and objectively punishment to the accused of money laundering. The law allows the State to remain in possession of the goods of the accused, independently of the stoppage of business activities and the consequent bankruptcy, just to facilitate the forfeiture of assets. Engenders the accused in true Kafkaesque process, where shall prevail the imbalance of the procedure in favor of the State, removing of the accused their Fundamental Rights and Guarantees. In this model, we revealed a critical analysis of the preservative measures in the Money Laundering Law, emphasizing some discrepancies capable of unconstitutionality of the current system, inconsistent with the Federal Constitution, concluding appeal for criminalization and prosecution of organized criminal activity, however, respecting the law and the Federal Constitution